THE INFLUENCE OF DOMESTIC INVESTMENT AND THE HUMAN DEVELOPMENT INDEX ON EMPLOYMENT OPPORTUNITIES IN CENTRAL KALIMANTAN - Harati, Rima (PT. Altin Riset Publishing, 2026)
The purpose of this study is to analyze the influence of domestic investment and the Human Development Index on employment opportunities in Central Kalimantan. This study was conducted in Central Kalimantan over the period 2015-2025. The analytical tools used were multiple regression analysis and classical assumptions, processed using SPSS 25. The results of the multiple regression analysis indicate that domestic investment and the Human Development Index have a significant influence on employment opportunities in Central Kalimantan. The results of the classical assumptions indicate that this regression model meets the assumption of normality, that there is no multicollinearity in the regression model, that there are symptoms of heteroscedasticity in the regression model used, and that there are no symptoms or problems of autocorrelation in the regression model.